PELATIHAN PEMBUATAN PRODUK SUSU PROBIOTIK-SARI BUAH BAGI KELOMPOK WANITA TANI DUSUN WONOREJO KOTA BATU - Nuzul Wahyuning Diyah (Universitas Negeri Surabaya, 2020)
The cow milk collected in KUD Batu has reached 16-17 tons per day. The most product is fresh dairy milk and only small amount of processed products. The target community had no experiences in processing cow milk using probiotic microbes yet. The objectives was transfering of science and technology about the production of probiotic milk combined with fruit juice. This program was specifically directed to increase the empowerment of Kelompok Wanita Tani